Measurement of Oxygen Concentration in Static and Flowing Liquid Pb-Bi by Using Zirconia Based Sensor - Adhi, Pribadi Mumpuni; Kamal, Dianta Mustofa; Muslimin, Muslimin; Vilcu, Andrei; Kondo, Masatoshi; Takahashi, Minoru (Indonesian Journal of Physics, 2020)
Liquid Lead-Bismuth Eutectic (LBE) has been proposed as one of the coolant for the Generation IV nuclear reactor. However, the oxygen should be controlled adequately to suppress the corrosion rate of the LBE. A device called oxygen sensor made of zirconia as solid electrolyte has been used to monitor the oxygen concentration online in order to control the oxygen concentration. The principle of this sensor is based on electrochemistry method where the difference oxygen activitiy between reference electrode (RE) and working electrode (in liquid LBE) can make potential difference. The potential difference is measured by electrometer and can be converted into oxygen concentration based on Nernst equation. Iron (Fe)/Magnetite (Fe3O4) was used as material for RE in this study. Measurement of oxygen concentration was conducted at 450 - 600°C for the static condition of LBE and around 390°C for the dynamic condition of flowing LBE. The oxygen concentration for both two experiment conditions were set in oxygen saturated condition of Pb-Bi. The oxygen sensor based on zirconia solid electrolyte with Fe/Fe3O4 as RE can measured the oxygen concentration in liquid LBE. The results showed that the measurement was agreed with the Nernst equation theoretical calculation.